Assessment of antimicrobial effects of food contact materials containing silver on growth of Salmonella Typhimurium. (February 2017) - Williams, Katherine; Valencia, Luis; Gokulan, Kuppan; Trbojevich, Raul; Khare, Sangeeta
Abstract: Food contact materials containing antibacterial properties are progressively appearing in the market. Items intended to provide antimicrobial effects such as increased shelf life and food safety are incorporating silver materials during the manufacture of such products. This study examined the total silver content, release capacity, and antibacterial activity of three different silver-containing food contact materials: plastic food storage containers, a plastic cutting board, and food wrapping paper. Silver content and release were determined by Inductively Coupled Plasma Mass Spectrometry, and the results showed that, although the amount of silver in each product was similar, migration varied considerably with kind of material and simulant choice. Antimicrobial effect was tested by measuring the growth of Salmonella Typhimurium during or after exposure to the different food contact materials. The results showed that the food storage containers and wrapping paper delayed the growth of S . Typhimurium under certain conditions, but that these effects were short-lived. The strain of S . Typhimurium used in this study was found to be negative for the presence of tested silver resistance genes. The results of this study suggest that a thorough investigation should be required to show/claim the efficacy of silver-containing food contact materials for food safety purposes. Graphical abstract: Highlights: Evaluated the silver content, release, and antimicrobial activity of Food Contact Materials (FCM) containing silver. Assessment of each FCM took into account its intended use and the inherent limitations of working with the material. Silver was present in all tested FCM and release was possible under certain conditions. Some FCM showed short-lived antibacterial activity against S . Typhimurium in terms of delayed growth of the organism. The S. Typhimurium strain was negative for the presence of tested silver resistance genes.